Pemanfaatan Limbah Serbuk Gergaji Sebagai Media Budidaya Jamur Tiram (Pleourotus Ostreatus L.) - Hadi Susilo; Riki Rikardo; Suyamto Suyamto (Universitas Mathla'ul Anwar Banten, 2017)
The development of the agricultural sector is not only food crops, but also plantation crops and horticulture. One of horticulture crops that have contributed to human is oyster mushroom. Oyster mushroom is highly suitable for people of Indonesia that is still difficult to meet the needs complete nutrition, especially protein needs. Contains essential amino acids: arginine, histidine, isoleucine, lysine, methionine, phenylalanine, threonine, tryptophan, valine, unsaturated fats, vitamin B1, B2, niacin, biotin, micro and macro elements. The oyster mushroom is also shown to be potent inhibitors of HIV-AIDS, cholesterol, blood sugar and cancer. Mushroom cultivation media requires for growth. In this study utilizes waste sawdust which there are many in the community with the goal of increasing the economic value and the standard of life. Cultivation starts from media preparation, sterilization, filling and incubation seed to harvest. Wet harvest oyster mushrooms for 5 weeks increased gradually. 1000 new baglogs, 750 baglogs already can produce 290 kilograms of harvested oyster mushrooms wet. The selling price is Rp 9,000 and total revenue is Rp 2.61 million for one month. Mushroom cultivation should be accompanied by the processing of waste in order to have a double added value of improving economic value and overcome the environment. Based on the data and the results of the discussion showed that the oyster mushroom cultivation can work well and provide benefits, so as to improve the economy for the community.